Model Blended Learning pada Diklat Teknis Substantif Tematik Madrasah Ibtidaiyah - Asih Aryani (Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan, 2021)
[BLENDED LEARNING MODEL IN SUBSTANTIVE THEMATIC TECHNICAL TRAINING OF MADRASAH IBTIDAIYAH]. This study aims to determine the response and increase in learning outcomes of participants in the Thematic Substantive Technical training at Madrasah Ibtidaiyah in Blended Learning. The research approach used is descriptive qualitative with a sample of 60 people, the instruments used were observation, documentation, and closed questionnaires. The learning process is carried out in five stages, namely: live event, self-paced learning, collaboration, assessment, and performance support material. The results show that; 98% of participants were happy with the application of Blended Learning, 75% of participants admitted that it was easy to understand the training material presented in Blended Learning, and 90% of participants felt that the Blended Learning model used was effective. There was an increase of 13,49 (23.4%), namely an increase from the pre-test score with an average of 57.67 to the post-test with an average of 71.16.